Differences In D-Dimer Levels of Moderate And Severe Covid-19 Patients Treated At Hajj Adam Malik Hospital, Medan - Denny Hadi; Jelita Siregar; Noni Novisari Soeroso; Asgar M. Nafchi (International Journal of Health and Pharmaceutical (IJHP), 2025)
An outbreak of coronavirus disease 2019 (COVID-19), initially reported in December 2019 in Wuhan, Hubei Province, China, emerged as a mysterious pneumonia caused by the novel β-coronavirus, 2019-nCoV. Among hospitalized COVID-19 patients, elevated D-dimer levels and impaired hemostasis have been commonly observed, often associated with disease severity and mortality. This study aimed to assess differences in D-dimer levels among mild, moderate, and severe COVID-19 patients in a cross-sectional design involving 36 confirmed COVID-19 patients hospitalized at H. Adam Malik General Hospital Medan. Conducted from August to October 2021 at the Departments of Clinical Pathology and Pulmonology and Respiratory Medicine, the study used consecutive sampling. The participants had an average age of 50.92 years, with hypertension and diabetes mellitus being the most common comorbidities. The average D-dimer level was 1324.28 ng/mL (SD = 2360.45 ng/mL), ranging from 100 ng/mL to 13,420 ng/mL. A significant difference in D-dimer levels was observed between patients with moderate and severe COVID-19, highlighting its potential role in evaluating disease progression and severity.